Selective laser melting (SLM) of AlSi12Mg lattice structures. (15th May 2016) - Leary, Martin; Mazur, Maciej; Elambasseril, Joe; McMillan, Matthew; Chirent, Thomas; Sun, Yingying; Qian, Ma; Easton, Mark; Brandt, Milan
Abstract: Additive manufacture (AM) enables innovative structural design, including the fabrication of complex lattice structures with unique engineering characteristics. In particular, selective laser melting (SLM) is an AM process that enables the manufacture of space filling lattice structures with exceptional load bearing efficiency and customisable stiffness. However, to commercialise SLM lattice structures it is necessary to formally define the manufacturability of candidate lattice geometries, and characterise the associated mechanical response including compressive strength and stiffness. This work provides an experimental investigation of the mechanical properties of SLM AlSi12Mg lattice structures for optimised process parameters as well as the manufacturability of lattice strut elements for a series of build inclinations and strut diameters. Based on identified manufacturability limits, lattice topologies of engineering relevance were fabricated, including both stretch-dominated and bending-dominated structures. Manufactured lattice morphology and surface roughness was quantified, as were the associated mechanical properties and deformation and failure behaviour. Graphical abstract: Highlights: Processing parameters for AlSi12Mg are proposed. Manufacturability limits are quantified to allow robust AlSi12Mg lattice design. AlSi12Mg lattice failure modes are experimentally and numerically assessed. Energy absorption and geometric fidelity are quantified. Young's modulus is lower than unloading modulus for all specimens.